Regulation of Ionic Distribution and Desolvation Activation Energy Enabled by In Situ Zinc Phosphate Protective Layer toward Highly Reversible Zinc Metal Anodes - Zhang, Shengzhao; Ye, Minghui; Zhang, Yufei; Tang, Yongchao; Liu, Xiaoqing; Li, Cheng Chao (Advanced functional materials, 2023)
Despite the merits of high specific capacity, low cost, and high safety, the practical application of aqueous Zn metal batteries (AZMBs) is plagued by the dendritic growth and corrosion reaction of Zn metal anodes. To solve these issues, a Zn3(PO4)2·4H2O protective layer is in‐situ constructed on Zn foil (Zn@ZnPO) by a simple hydrothermal method, avoiding the traditional slurry‐casting process. The insulating and conformable ZnPO layer improves the wettability of Zn@ZnPO and aqueous electrolyte via decreasing the contact angle to 11.7o. Compared with bare Zn, the Zn@ZnPO possesses a lower desolvation activation energy of 35.25 kJ mol‐1, indicating that the ZnPO fasters the desolvation of hydrated Zn2+ ions and thereby ameliorates their transport dynamics. Micro‐morphology and structural characterization show that there are no dendrites forming on the post‐cycling Zn@ZnPO anodes, and the interfacial ZnPO layer remains almost identical before and after cycles. It can be explained that the electrochemically stable ZnPO layer acts as an ionic modulator to enable the homogeneous distribution of Zn2+ ions, inhibiting the growth of Zn dendrites. Benefiting from these advantages, the Zn@ZnPO based symmetric and full cells deliver highly reversible Zn plating/stripping behavior and long cycling lifespans. A conformable and insulating protective layer of Zn3(PO4)2·4H2O is in situ formed on a zinc metal anode. By homogenizing the distribution of Zn2+ ions, reducing desolvation activation energy and depressing parasitic reaction via repelling H2O, a non‐dendritic and long‐life aqueous zinc metal battery is achieved.